An interrogation of research on Caribbean social issues: establishing the need for an indigenous Caribbean research approach. (March 2019) - Wilson, Shakeisha; Nakhid, Camille; Fernandez-Santana, Anabel; Nakhid-Chatoor, Margaret
Caribbean social issues, like so many other global issues, are often researched and addressed using traditional Western philosophies and methodologies. However, some societies have criticized the use of Western approaches recognizing their unsuitability to accurately assess the distinctive culture, identity, and overall social structures of these societies. An investigation of the use of Caribbean research methodologies or approaches revealed that there is a significant absence in the use of culturally specific ways of conducting research in the Caribbean region and diaspora. This pattern was found to be consistent with the authors' findings from a critical review of research methodologies used by postgraduate scholars in investigating Caribbean-related issues in the past 10 years. As a result, this article lobbies for the promotion of more culturally specific and relevant Caribbean research approaches that are respectful of the worldviews and practices of locals within the region.